A new record of horse hair blight on nutmeg (Myristica fragrans Houtt.) from India - Samuel Mathew, P P Joy, Baby P Skaria, Sajitha Kumari, J Thomas (Journal of Spices and Aromatic Crops, 2000)
A new record of horse hair blight disease caused by Marasmius equicrinis on nutmeg (Myristica fragrans) observed at Rayamangalam Panchayat of Emakulam District in Kerala, India, is reported. The formation of mycelial hairs on the plant caused drying of leaves and branches getting themselves hung on the mycelial network giving a ’bird’s nest’ appearnce.